Implementasi Video Animasi 3D Sebagai Media Branding Produk Usaha Mikro, Kecil, dan Menengah Pada Qusnadi Proyektor 889 - Lahagu, Edita Emilia; Marbun, Nasib (STIKOM Tunas Bangsa Pematangsiantar, 2024)
The development of increasingly advanced technology makes micro, small and medium business owners increasingly challenged to develop branding that can differentiate from other businesses. Qusnadi Proyekto 889 is one of the micro, small, and medium enterprises that focuses on projector sales. So far, Qusnadi Proyektor 889 uses a sales link as a branding and promotional media, so it has many limitations such as potential consumers cannot access the link which makes consumers do not know clear information about the products being sold. For this reason, by creating an animated video as a media branding and promotion of projectors at Qusnadi Proyektor 889, it is hoped that it will have an impact on increasing sales and can strengthen brand image. 3D animation is made using the Blender application and the resulting output is a 3D animation video as a media branding and promotion of the Cheerlux C9 TV Tuner projector at Qusnadi Projector 889 which displays the kenggulan of the projector. In this study the authors created a 3D animation using the concept of the Multimedia Development Life Cycle (MDLC) method which consists of six stages, namely concept, design, material collecting, assembly, testing, distribution, and distribution. The result of this research is a 3D animation video that helps promote the Cheerlux C9 TV Tuner Projector. It is hoped that this video can help micro, small and medium enterprises Qusnadi Proyektor 889 to grow and succeed in the projector industry